EFEK RETEMPERING TERHADAP KUAT TEKAN BETON - ISTIATUN SUKARNO; DJEDJEN ACHMAD (Politeknik Negeri Jakarta, 2014)
ABSTRACT Have been investigated the impact of the retempering at concrete compressive strength. Retempering is adding water to the concrete mixture which already began to stiffen in the hope that the concrete is still workable. Research was done at concrete with the quality of k 225, slump value of 60-180 mm, which is in retempering with water, and concrete in retempering with water and cement. Retempering was done on concrete that has been delayed casting within 60 minutes, 120 minutes, 180 minutes and 240 minutes. The result in concrete at retempering with water decreased compressive strength, along with the addition of water. While the concrete is in retempering with water and cement with water-cement ratio (w/c) is constant, the relative compressive strength of concrete is not much different from the reference. The difference is about 4% of the compressive strength of concrete reference. ABSTRAK Telah diteliti dampak retempering terhadap kuat tekan beton. Retempering adalah penambahan air ke dalam campuran beton yang sudah mulai kaku dengan harapan beton tersebut masih dapat dikerjakan. Penelitian dilakukan pada beton dengan mutu k 225, nilai slump 60 – 180 mm, yang di retempering dengan air, dan beton yang di retempering dengan air dan semen. Retempering dilakukan pada beton yang telah didiamkan dalam waktu 60 menit, 120 menit, 180 menit dan 240 menit. Hasilnya pada beton yang di retempering dengan air mengalami penurunan kuat tekan, seiring dengan penambahan air. Sedangkan pada beton yang di retempering dengan air dan semen dengan faktor air semen (fas) konstan, kuat tekannya relatif tidak jauh berbeda dengan beton referensi. Perbedaannya kurang lebih 4 % dari kuat tekan beton referensi. Kata kunci : beton, retempering, kuat tekan, slump.